A new species of Strotarchus Simon, 1888 from Honduras (Araneae, Cheiracanthiidae) - Cubas-Rodriguez, Alex M.; Bonaldo, Alexandre B.; Brescovit, Antonio D. (Zootaxa, 2023)
A new species, Strotarchus chamevazquezi sp. nov., is described based on both sexes from Department Francisco Morazán, Honduras. A detailed description, diagnosis, photographs, and distribution map of the new species are given. This is the first species of this genus recorded from Honduras.